2005
DOI: 10.3171/foc.2005.19.6.7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic-assisted repair of craniosynostosis

Abstract: Object The goal of the craniofacial surgeon has always been the correction of form and function with prevention of associated morbidity and death. Through the pioneering work of Jimenez and Barone, minimally invasive approaches to the surgical correction of craniosynostosis are now gaining wider acceptance. Here the authors review the technique for endoscopic-assisted repair of craniosynostosis from the perspective of a new minimally invasive approach. They also asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
35
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(39 citation statements)
references
References 22 publications
(16 reference statements)
3
35
0
1
Order By: Relevance
“…It is suggested that this strategy is associated with a reduction in blood loss and transfusions, duration of hospital stay, and cost, as compared with other calvarial remodeling procedures. 1,[6][7][8][9]11 These 6 cited studies include more than 350 patients. Of these patients, 5 had nonsyndromic fusion of new sutures following the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that this strategy is associated with a reduction in blood loss and transfusions, duration of hospital stay, and cost, as compared with other calvarial remodeling procedures. 1,[6][7][8][9]11 These 6 cited studies include more than 350 patients. Of these patients, 5 had nonsyndromic fusion of new sutures following the initial surgery.…”
Section: Discussionmentioning
confidence: 99%
“…While open correction produces excellent results, blood loss and a long surgical duration may lead to complications in the child. 15,22 More recently, newer endoscopic minimally invasive techniques have been described for the treatment of craniosynostosis with the aim to minimize blood loss during surgery. 18 Jimenez and Barone first described the endoscopically assisted craniectomy for craniosynostosis in 1998.…”
Section: 4101317mentioning
confidence: 99%
“…In endoscopic craniectomy, the operation is performed by small incisions in the skin and endoscopes are used to expose the different areas of the affected suture and perform cranial vault remodeling. 9,15 While the endoscopic techniques allow less blood loss, they are suited for infants. It is indeed interesting to note how the strip craniectomy first described by Lannelongue has evolved into the present-day techniques of cranial vault remodeling.…”
Section: 4101317mentioning
confidence: 99%
“…Тригоноцефалия встречается в 10% случаев [10,11], чаще (75-85%) у мальчиков [8]. Данный вид краниосино-стоза может иметь генетическую природу вследствие ано-малий хромосом 3, 9, 11 и сочетаться с другими аномалия-ми развития нервной системы [12,13].…”
unclassified